Combined Effect of Pesticides Containing Active Ingredients of Chlorpyrifos and Mancozeb on the DNA Damage of Chlorella Sorokiniana Shihira and Krauss - Nadar, Y. E.; Nugroho, A. P. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
The intensive use of pesticides in agricultural areas can leave residues of pesticide mixtures on the soil surface. Surface run-off can carry pesticide residues, enter water bodies, and then may affect non-target organisms. Chlorpyrifos and mancozeb are active ingredients commonly contained in pesticides applied in shallot farming. This study aims to evaluate the combined effect of pesticides containing active ingredients of chlorpyrifos and mancozeb on the growth and DNA damage of the microalgae Chlorella sorokiniana. The test organism was exposed to the combined concentration of chlorpyrifos:mancozeb, i.e., 0:0, 20%:20%, 20%:80%, 80%:20%, and 80%:80% of the individual EC50 of each pesticide with sampling time at hours 0, 6, 24, and 48. Microalgae growth was estimated by cell counting method, and DNA damage was analyzed by alkaline comet assay method with parameters, i.e., Tail Intensity (TI%), Head Intensity (HI%), Tail Moment (TM), Olive Tail Moment (OTM), and Tail Factor (TF). The results showed that the combined pesticides inhibited the growth of C. sorokiniana, with the highest growth inhibition being at a combined concentration of 80%:80%. The TM and OTM values of C. sorokiniana increased with the increase of combined concentrations at an exposure period of up to 24 hours. In conclusion, the combined exposure could induce growth inhibition and DNA damage of Chlorella sorokiniana, mainly in the first 24 hours. The TM and OTM can be used as sensitive biomarkers for biomonitoring pesticide pollution.